Endothelial and platelet microparticles in patients with antiphospholipid antibodies. Issue 2 (February 2015) - Breen, K.A.; Sanchez, K.; Kirkman, N.; Seed, P.T.; Parmar, K.; Moore, G.W.; Hunt, B.J.
Abstract: Background: The antiphospholipid syndrome (APS) is the association of thrombosis and recurrent pregnancy loss and/or pregnancy morbidity with persistent antiphospholipid antibodies (aPL). Previous studies of microparticles in patients with APS/aPL have mainly been small and findings, contradictory. Objectives: To quantify endothelial and platelet microparticle levels in patients with isolated antiphospholipid antibodies or primary antiphospholipid syndrome (PAPS). Patients/Methods: We measured endothelial and platelet microparticle levels by flow cytometry in 66 aPL/PAPS patients and 18 healthy controls. Results: Levels of circulating platelet (CD41 and CD61) and endothelial microparticles (CD51 and CD105) were significantly increased in patients with PAPS and aPL compared to healthy controls. There were correlations between platelet and endothelial microparticles levels in all patients with aPL. Conclusions: Platelet and endothelial microparticles are increased in all patient groups within this cohort of patients aPL. Whether they may have a role in the pathogenesis of APS merits further study. Highlights: We studied platelet and endothelial microparticles in patients with aPL/PAPS. Patients included had thrombotic, obstetric APS or isolated aPL. Endothelial and platelet microparticles levels were increased in these patients. Thrombotic APS patients (not obstetric APS or isolated aPL) had increased levels. No differences in microparticle procoagulant activity was found in these patients.